The effect of clinical interventions on the oral health‐related quality of life in older adults. (9th August 2022) - Ky, J; Scepanovic, T; Senthilvadevel, N; Mati, S; Ming, ALC; Ng, M; Nguyen, D; Yeo, P; Zhao, T; Paolini, R; Lim, MAWT; Celentano, A
Abstract: This paper reviews the literature to assess the effectiveness of oral health interventions in influencing oral health‐related quality of life (OHRQoL) in older adults. Clinical studies published in 2010 onwards reporting oral health interventions in older adults and subsequent changes in OHRQoL were systematically searched in Medline, Web of Science and EMBASE databases. Reporting followed Preferred Reporting Items for Systematic Review and Meta‐Analysis criteria. Eligibility evaluation and data abstraction from eligible studies were guided by predefined PICO questions and bias assessment by the Quality in Prognosis Studies tool. The search retrieved 144 articles. Of the 20 articles that met the eligibility criteria, 45% (9) reported a statistically significant improvement in OHRQoL. The majority of studies were conducted in adults with complete edentulism (70%) and mainly focused on implant provision to support a removable prosthesis (30%). The search indicates the limited scope of current literature on geriatric dental interventions, focusing mainly on denture realignments, denture fabrication and implant placement. Although the majority of the oral health interventions focused on edentulism and removable prostheses, there are many areas of oral health interventions and their potential impact on OHRQoL in this demographic group that have yet to be explored. © 2022 Australian Dental Association.